ANALYSIS OF CORPORATE GOVERNANCE OF CONVENTIONAL BANKS AND ISLAMIC BANKS IN INDONESIA - Nurfadilah; Agusdiwana Suarni; Sahrullah (Journal on Islamic Economics, Finance & Banking [Z-CONOMICS], 2025)
This study aims to analyze and compare the implementation of corporate governance between conventional and Islamic banks in Indonesia during the 2019-2023 period. The type of data used in this study is secondary data, namely annual data obtained from annual reports published on the official website of the Indonesia Stock Exchange (IDX) as well as conventional and Islamic banks in Indonesia. Data collection was conducted through library research and internet research. The data analysis methods used in this study are descriptive statistical tests and two-average hypothesis tests (independent sample t-tests). Five indicators are used: board size, use of Big 4 auditors, number of board meetings, presence of foreign directors, and gender proportion. Through descriptive statistical tests and independent sample t-tests, it was found that there were no significant differences between the two types of banks in corporate governance variables. This finding indicates the homogeneity of governance structures in the Indonesian banking sector, both conventional and Islamic. This study contributes to the corporate governance literature by describing the role of transparency and diversity principles in supporting banking digitalization.